2015
DOI: 10.3390/su70810098
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprints and Embodied Carbon Flows Analysis for China’s Eight Regions: A New Perspective for Mitigation Solutions

Abstract: Carbon footprints have been widely employed as an indicator for total carbon dioxide released by human activities. In this paper, we implemented a multi-regional input-output framework to evaluate the carbon footprints and embodied carbon flows for the eight regions of China from consumption-based perspective. It is found that the construction, electricity/stream supply, and machine manufacturing rank as the top sectors with the largest total carbon emissions. The construction sector alone accounts for 20%-50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…It is clearly shown that electricity is another noticeable contributor in the humid regions, and especially in the arid NW (Figure 3), and its contribution to GHG emissions becomes of importance when the farmers' fertilization practice is becoming rationale [19]. In these regions, electricity consumption was mainly for irrigation by electricity-driven pumps, which had generated a great deal of CO 2 emissions [40]. As a solution, it is of great significance to renovate irrigation systems and improve water and fertilizer use efficiency in the peach orchard, since the CF could be thus decreased by water-saving irrigation [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clearly shown that electricity is another noticeable contributor in the humid regions, and especially in the arid NW (Figure 3), and its contribution to GHG emissions becomes of importance when the farmers' fertilization practice is becoming rationale [19]. In these regions, electricity consumption was mainly for irrigation by electricity-driven pumps, which had generated a great deal of CO 2 emissions [40]. As a solution, it is of great significance to renovate irrigation systems and improve water and fertilizer use efficiency in the peach orchard, since the CF could be thus decreased by water-saving irrigation [40].…”
Section: Discussionmentioning
confidence: 99%
“…In these regions, electricity consumption was mainly for irrigation by electricity-driven pumps, which had generated a great deal of CO 2 emissions [40]. As a solution, it is of great significance to renovate irrigation systems and improve water and fertilizer use efficiency in the peach orchard, since the CF could be thus decreased by water-saving irrigation [40]. Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…A production process may require intermediate products or services from other sectors externally or locally, for example, clothes' production in region r may require raw material from region s. In order to track the real ecological appropriation (land use appropriation or carbon emission), we can decompose the TPCCs by region and then by sector [14,19].…”
Section: Decomposition Of Total Product Consumption Coefficients (Tpcmentioning
confidence: 99%
“…For example, the China regional level ETSs have been implemented in seven provinces as pilot schemes since 2013 [26][27][28]. The electricity sector in China is also heavily regulated by the government, and the carbon costs cannot be easily passed on to consumers, which may be a cause of market distortions [6,27,28].…”
Section: Distinctive Features Of the Korean Etsmentioning
confidence: 99%